Underwater Noises of Open-Circuit Scuba Diver - Vladimir KORENBAUM; Anatoly KOSTIV; Sergey GOROVOY; Veniamin DOROZHKO; Anton SHIRYAEV (Archives of Acoustics, 2020)
The features of respiratory noises and noises of fins for open-circuit scuba divers, indicating a multipole character of noises emission, are specified in cameral conditions. It demonstrates a possibility to detect low-frequency components of noises of fins with pressure gradient sensor in near field. A possibility of estimating the respiratory rate of an open-circuit scuba diver is demonstrated at distances up to 100 m in real sea. It gives an opportunity of estimating the bearing (time delay in a pair of hydrophones) for the open-circuit scuba diver by respiratory noises at distances up to 150 m in real sea. Thus, low-frequency underwater noises of open-circuit scuba divers may be successfully applied to monitor the safety of diving and to prevent waterside intrusion by trespassers.